Effectiveness and safety of Levofloxacin containing regimen in the treatment of Isoniazid mono-resistant pulmonary Tuberculosis: a systematic review - Inbaraj, Leeberk Raja; Shewade, Hemant Deepak; Daniel, Jefferson; Srinivasalu, Vignes Anand; Paul, Jabez; Satish, S.; Kirubakaran, Richard; Padmapriyadarsini, Chandrasekaran (Frontiers in Medicine, 2023)
Background We aimed to determine the effectiveness and safety of the Levofloxacin-containing regimen that the World Health Organization is currently recommending for the treatment of Isoniazid mono-resistant pulmonary Tuberculosis. Methods Our eligible criteria for the studies to be included were; randomized controlled trials or cohort studies that focused on adults with Isoniazid mono-resistant tuberculosis (HrTB) and treated with a Levofloxacin-containing regimen along with first-line anti-tubercular drugs; they should have had a control group treated with first-line without Levofloxacin; should have reported treatment success rate, mortality, recurrence, progression to multidrug-resistant Tuberculosis. We performed the search in MEDLINE, EMBASE, Epistemonikos, Google Scholar, and Clinical trials registry. Two authors independently screened the titles/abstracts and full texts that were retained after the initial screening, and a third author resolved disagreements. Results Our search found 4813 records after excluding duplicates. We excluded 4769 records after screening the titles and abstracts, retaining 44 records. Subsequently, 36 articles were excluded after the full-text screening, and eight appeared to have partially fulfilled the inclusion criteria. We contacted the respective authors, and none responded positively. Hence, no articles were included in the meta-analysis. Conclusions We found no 'quality' evidence currently on the effectiveness and safety of Levofloxacin in treating HrTB.